PENGARUH KEBIJAKAN DIVIDEN, PAJAK PENGHASILAN DAN FAKTOR LAINNYA TERHADAP INCOME SMOOTHING - Christina, Silvy; Handojo, Irwanto; Djahsan, Indra Arifin (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The research on Income Smoothing is to obtain empirical evidence about the influence of dividend policy, income tax, firm size, profitability, leverage, firm value, managerial ownership, and public ownership on income smoothing. This Research population is non-financial firms listed in the Indonesia Stock Exchange from 2020 until 2022. There are 55 companies selected as samples by using the purposive sampling method. The samples are tested and analyzed using the logistic regression method. The result of this research implies that income tax, firm size, profitability, leverage, firm value, managerial ownership, and public ownership have no significant influence on income smoothing, while dividend policy has positive influence on income smoothing.